2022
DOI: 10.1155/2022/9084334
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Antimicrobial Resistance of Staphylococcus Species from Chicken, Chicken Litter, and Humans in Addis Ababa, Ethiopia

Abstract: Background. In veterinary medicine, three Staphylococcus species are of particular importance as primary causes of specific diseases; S. aureus (mastitis in ruminants, equine botryomycosis, and bumble foot in poultry), S. hycus (porcine exudative epidermitis), and S. intermedius (canine pyoderma). The disease conditions caused by Staphylococcus in poultry vary with site, route, and predisposing factors include wounds as a result of fighting/cannibalism, immunosuppression based on virus infection or parasite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
1
1
Order By: Relevance
“…The present study revealed that CoNS species were isolated at rate of 28.6%. The result was lower than the report of Enquebaher et al [27] in the Tigray region, Zeryehun and Abera [28] in selected districts of Eastern Harrarghe who reported 51.6% and 34.2% prevalence respectively, and higher than the reports of Gizaw et al [29], Abunna et al [30], Fesseha et al [31] who reported 9.6%, 15% and 12.5% prevalence of CoNS species in Oromia, in and around Addis Ababa and in Modjo Town and Suburbs, Central Oromia respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The present study revealed that CoNS species were isolated at rate of 28.6%. The result was lower than the report of Enquebaher et al [27] in the Tigray region, Zeryehun and Abera [28] in selected districts of Eastern Harrarghe who reported 51.6% and 34.2% prevalence respectively, and higher than the reports of Gizaw et al [29], Abunna et al [30], Fesseha et al [31] who reported 9.6%, 15% and 12.5% prevalence of CoNS species in Oromia, in and around Addis Ababa and in Modjo Town and Suburbs, Central Oromia respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The present study revealed that CoNS species were isolated at a rate of 28.6%, (83/290), 95% CI: 23.5–34.2). The result was lower than the report of Enquebaher et al [ 19 ] in the Tigray region, Zeryehun and Abera [ 61 ] in selected districts of Eastern Harrarghe, Balemi et al [ 6 ] in two pastoral districts Southern Ethiopia who reported 51.6%, 34.2% and 39% prevalence respectively, and higher than the reports of Gizaw et al [ 28 ], Abunna et al [ 1 ], Fesseha et al [ 23 ] who reported 9.6%, 15% and 12.5% prevalence of CoNS species in Oromia, in and around Addis Ababa and in Modjo Town and Suburbs, Central Oromia respectively. A higher isolation rate of CoNS species from milk might be associated with the CoNS being prominent biofilm producers [ 29 , 36 ] which enhances the bacteria to resist antibiotics and evade immune system mounting.…”
Section: Discussioncontrasting
confidence: 62%
“…They lessen the feed conversion ratio, weight growth, egg production, and septicemia, which has significant economic ramifications [14]. A comparable investigation was undertaken in Addis Ababa, Ethiopia, when 12.9% of S aureus was recovered from chicken cloacal swabs [15]. In a comparable research performed in Bogor Regency, Indonesia, 28% of S. aureus was retrieved from broiler chicken cloacal swabs and 50% was isolated from layer chicken cloacal swabs [16].…”
Section: Introductionmentioning
confidence: 99%